Um olhar voltado ao desenvolvimento do pensamento geométrico em alunos do ensino fundamental por meio de atividades práticas - Manfio, Carine Girardi (2015)
This paper refers to an research that sought to develop geometric thinking students in the sixth grade of elementary school from practices. The school activities in which it was held that job belongs to the Municipal network of Júlio de Castilhos Education, it is located on the outskirts of this city. The activities were proposed in order to provide the student with the construction of some basic, concepts and definitions of geometry from the geometric objects classification. The classification user as a basic criterion the predominant characteristics of each geometric object, which is the geometric figures or not they belong to the same class in adition, students to develop the proposed activities worked in groups, following the criteria proposed by the joint assimilation.